Peripheral labour market position and risk of disability pension: a prospective population-based study. Issue 8 (20th August 2014) - Gustafsson, Klas; Aronsson, Gunnar; Marklund, Staffan; Wikman, Anders; Floderus, Birgitta
Abstract : Objective: To investigate what impact individuals' position in a labour market core–periphery structure may have on their risk of disability pension (DP) in general and specifically on their risk of DP based on mental or musculoskeletal diagnoses. Methods: The study comprised 45 567 individuals who had been interviewed for the annual Swedish Surveys of Living Conditions (1992–2007). The medical DP diagnoses were obtained from the Swedish Social Insurance Agency (1993–2011). The assumed predictors were studied in relation to DP by Cox's proportional hazards regression. The analyses were stratified on sex and age, controlling for social background and self-reported long-standing illness at baseline. Results: All three indicators underlying the categorisation of the core–periphery structure: employment income, work hours and unemployment, increased the risk of DP in all strata. The risk of DP tended to increase gradually the more peripheral the labour market position was. The risk estimates for DP in general and for DP based on mental diagnoses were particularly high among men aged 20–39 years. Conclusions: The core–periphery position of individuals, representing their labour market attachment, was found to be a predictor of future DP. The association was most evident among individuals below 40 years of age with regard to DP based on mental diagnoses. This highlights the need for preventative measures that increase the participation of young people in working life.